Pengaruh Pelayanan Terhadap Loyalitas Pelanggan Studi Kasus pada PT Setia Anugerah Motor - Sujana, Sujana; Zebua, Amenesia (Jurnal Ilmiah Ranggagading (JIR), 2011)
Tougher competition market nowadays has made market participants race and compete to be able to servive in business due to the amount of similar business participans in Bogor. The competition can be assumed as a âwar of movementâ. In all cases, success is determined by how does the company anticipate the market and respose the change of consumersâ need and behaviour. Because of the tough competiton as mentioned above, the companies will find it difficult to increase the amount of customers. The customers will evaluate their consumption until they feel that they have sense of satisfaction or not. There are many products of high quality and plus value offered by competitors, so itâs difficult to fetch competitorsâ market segment. Doing various of efforts to maintain market with better services to raise customersâ loyalty is the better alternative. The purpose of this research is to find out (1) the services implemented by the company; (2) the current condition of the companyâs services; (3) the correlation between services and customersâ loyalty; (4) the companyâs strategy to get customersâ loyalty. The result of this study shows that the influence of services to customersâ loyalty has a good perception. From the analysis of the effect of services to the customersâ loyalty, it can be found out that function Y = 36,2019 + 0,2857 X. The result of correlation coefficient analysis shows r = 0,2260; it means that there is positive and significant correlation. Significance test to the two sides yields t-count (2,5427) > t-table (1660); it means Ho stating that there is no correlation between services and customersâ loyalty is rejected and Ha stating that there is correlation between services and customersâ loyalty is accepted. The result of determination coefficient analysis shows that the services contribute 5,11% in influencing customersâ loyalty and the rest, that is 94,89%, is influenced by the other factors.